Revitalizing Photoaging Skin through Eugenol in UVB-Exposed Hairless Mice: Mechanistic Insights from Integrated Multi-Omics - Tao Tong; Ruixuan Geng; Seong-Gook Kang; Xiaomin Li; Kunlun Huang (MDPI AG, 2024)
Chronic ultraviolet (UV) exposure causes photoaging, which is primarily responsible for skin damage. Nutritional intervention is a viable strategy for preventing and treating skin photoaging. Eugenol (EU) presents anti-inflammatory and antioxidant properties, promotes wound healing, and provides contact dermatitis relief. This study explored the ability of EU to mitigate skin photoaging caused by UVB exposure in vitro and in vivo. EU alleviated UVB-induced skin photodamage in skin cells, including oxidative stress damage and extracellular matrix (ECM) decline. Dietary EU alleviated skin photoaging by promoting skin barrier repair, facilitating skin tissue regeneration, and modulating the skin microenvironment in photoaged mice. The transcriptome sequencing results revealed that EU changed the skin gene expression profiles. Subsequent pathway enrichment analyses indicated that EU might reverse the pivotal ECM-receptor interaction and cytokine-cytokine receptor interaction signaling pathways. Furthermore, EU alleviated the intestinal dysbiosis induced by chronic UVB exposure. Spearman analysis results further revealed the close connection between gut microbiota and skin photoaging. Considering the near-inevitable UVB exposure in modern living, the findings showed that the EU effectively reverted skin photoaging, offering a potential strategy for addressing extrinsic skin aging.